Attitude and behaviour of contractor in managing waste management in construction - Muhammad Farid Aiezat, Abdul Hamid (2018)
In Malaysia, there are very uncommon research have been done regarding the issue of attitude and behaviour of contractor in managing waste management in construction. A parcel of land may the proper way for local councils to be provided to contractors since they are lazy to dump their construction waste legally (The Star Online, 2016). There are three objectives in this research. Firstly, to study attitude and behaviour of contractor in managing construction waste. Secondly, to obtain the effect of contractor’s attitude and behaviour in managing construction waste. Thirdly, to analyse the solution to minimize construction waste. Since, the study is related to contractor, the primary target group is the contractor G7 and 56 respondents successfully got the respond from questionnaire. Construction sites are chosen around Kuantan, Pahang because of the increasing development percentage in Kuantan, Pahang. Microsoft Excel software is used to interpret and demonstrated the data as indicated by information from the questionnaire. The Relative Importance Index method, (RII) methods empower to figure out the crude information accurately got from the questionnaire. Overall the highest data analysis for attitude of contractor is a contractor give low wages to workers while for behaviour of contractor is a wrong material storage category. The recommendation of this research is to implement Industrial Building System (IBS) in project. Construction Industry Development Board Malaysia (CIDB) wants to make the Industrialised Building System (IBS) mandatory by 2020. Lastly, future research of this study is to use Building Information Modelling (BIM). The government is set to enforce the Building Information Modelling (BIM) for construction of public projects above RM100 million by 2019.